2022
DOI: 10.7554/elife.74535
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoregulation accommodates Type III secretion and assembly of a tether of ER-Chlamydia inclusion membrane contact sites

Abstract: Membrane contact sites (MCS) are crucial for nonvesicular trafficking-based interorganelle communication. Endoplasmic reticulum (ER)–organelle tethering occurs in part through the interaction of the ER resident protein VAP with FFAT motif-containing proteins. FFAT motifs are characterized by a seven amino acidic core surrounded by acid tracks. We have previously shown that the human intracellular bacterial pathogen Chlamydia trachomatis establishes MCS between its vacuole (the inclusion) and the ER through exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…Through gain- and loss-of-function studies, we showed that the C. trachomatis inclusion membrane protein IncS Ct interacts with, recruits, and colocalizes with STIM1 at the inclusion, thus identifying IncS Ct as a novel component of ER-inclusion MCS. Identification of the IncS Ct -STIM1 complex is in line with the current model that ER-inclusion MCS localized protein complexes are composed of specific inclusion membrane proteins that each interact with a defined set of host factors ( 17 , 24 , 25 ).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Through gain- and loss-of-function studies, we showed that the C. trachomatis inclusion membrane protein IncS Ct interacts with, recruits, and colocalizes with STIM1 at the inclusion, thus identifying IncS Ct as a novel component of ER-inclusion MCS. Identification of the IncS Ct -STIM1 complex is in line with the current model that ER-inclusion MCS localized protein complexes are composed of specific inclusion membrane proteins that each interact with a defined set of host factors ( 17 , 24 , 25 ).…”
Section: Discussionsupporting
confidence: 75%
“…While the respective role of the IncD-CERT-VAP and IncV-VAP complexes in lipid acquisition and ER-inclusion tethering is fairly well established ( 17 , 23 25 ), the role of the IncS Ct -STIM1 complex remains elusive. The concomitant expression and inclusion localization of IncS Ct with the recruitment of STIM1 to the inclusion, starting early and lasting throughout the C. trachomatis developmental cycle ( 26 ), are in line with a shared function for IncS Ct and STIM1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein purification and pulldowns were conducted as previously described ( 55 ) with minor modifications. Expression of GST-CETN2, MBP, MBP-CT105, or MBP-CT229 was induced overnight by the addition of isopropyl-β-thiogalactopyranoside (1 mM, final concentration) to a 1 L culture E. coli BL21-λDE3 at OD 0.8.…”
Section: Methodsmentioning
confidence: 99%
“…Intriguingly, the Chlamydia integral membrane proteins IncV and IncD tether the inclusion to the ER (Stanhope & Derre, 2018). IncV directly binds Vap on the ER through a FFAT motif (Stanhope et al , 2017), and the effector recruits the host protein kinase CK2 to the inclusion leading to the hyperphosphorylation of a FFAT motif core and serine‐rich segments immediately upstream of the noncanonical and canonical FFAT motifs, thus promoting the IncV‐Vap interaction (Ende et al , 2022). IncD indirectly makes contact to Vap through the FFAT motif‐containing host protein CERT (ceramide transfer protein; Derre et al , 2011; Elwell et al , 2011).…”
Section: Introductionmentioning
confidence: 99%